Glycerol-enhanced detection of a preferential structure latent in unstructured 1SS-variants of lysozyme - Noda, Yasuo; Narama, Kuniaki; Kasai, Kenichi; Tachibana, Hideki; Segawa, Shin-ichi (Biopolymers, 2012)
Four species of 1SS‐varinats of lysozyme were almost unstructured in water, judged from their near‐UV CD and 1H‐15N‐HSQC spectra. Some preferential structure might exist in such a disordered state, but the population of molecules in such a conformation must have been too small to be detected by spectroscopic methods. Indeed, our previous study showed that the addition of 30% glycerol induced the unstructured 2SS‐variant of lysozyme to form a native‐like structure. To extend this method to more disordered proteins, we attempted to detect some preferential structure latent in unstructured 1SS‐variants by the glycerol‐enhanced detection. Only in one molecular species of the four 1SS‐variants, 1SS[6‐127] containing a single disulfide bridge of Cys6‐Cys127, a preferential structure was found in the presence of 50% glycerol. It was detected by near‐UV CD measurements and the H/D exchange method combined with the NMR spectroscopy. The glycerol‐induced structure in 1SS[6‐127] was not localized only in the vicinity of Cys6‐Cys127, and largely protected regions distributed themselves among A‐, B‐, and C‐helices and Ile55 and Leu56. It was similar to the glycerol‐induced structure in 2SS[6‐127, 64‐80] containing two disulfide bridges of Cys6‐Cys127 and Cys64‐Cys80, although the former was less rigid than the latter. The role of A‐helix (residues 4–15) is proposed as an origin of excellent potential of Cys6‐Cys127 for inducing a tertiary structure in the α‐domain. © 2012 Wiley Periodicals, Inc. Biopolymers 97:539–549, 2012.